Behaviour of masonry walls strengthened with fibre-reinforced cementitious materials. Issue 4 (15th December 2021) - Celano, Thomas; Ceroni, Francesca; Lignola, Gian Piero
Abstract : Assessment of the mechanical properties of masonry materials is a key issue for evaluating the strength capacity of masonry walls. Two types of tests are usually adopted for experimentally evaluating the shear capacity of masonry walls: diagonal-compression and shear-compression tests. Different approaches are available in the literature for their interpretation. This paper reports an investigation into the behaviour of both unstrengthened and in-plane strengthened masonry walls with fibre-reinforced cementitious matrix materials under the two tests by means of a bi-dimensional non-linear-finite-element model. The model was first calibrated on the basis of comparisons with experimental results of diagonal-compression tests available in the literature. It was then used for comparing the numerical results obtained for the two tests in terms of local stress distributions for both unstrengthened and strengthened walls. The differences in the stress distributions in the tests, and the role of the reinforcement both on the distribution of stresses and on the global behaviour of the masonry walls, was highlighted.